THE SEARCH FOR SS433 OBJECTS: Hα PHOTOMETRY OF BLUE STARS IN M33 - Sholukhova, O. N. (Одеські астрономічні публікації, 2017)
ABSTRACT 549 blue stars with Ho; excess in the galaxy M 33 selected as candidates into unique objects of SS 433 and LBV (luminous blue variables) types are studied. These objects were divided by morphological types on Hog images in the following way: 81 stars, 154 diffuse nebulae, 180 bubble-type nebulae and 117 common intermediate objects. The diffuse objects are Hll regions with an exciting star. The bubbles are probably the envelopes around WR stars or the remnants of supernovae. Among the stars a group of 20 brightest ones is selected which by their average properties agree satisfactory with the parameters of blue super-supergiants or the objects of LBV type. The interstellar absorption determined by bright stars is equal to AV = 0.93 ± 0.05.